Association of Pulmonary Hypertension With Inflammation and Fluid Overload in Hemodialysis Patients - Yoo, Hugo Hyung Bok [UNESP]; Reis, Roberto dos [UNESP]; Telini, Wagner Moneda [UNESP]; Rodrigues-Telini, Lidiane [UNESP]; Hueb, Joao Carlos [UNESP]; Zanati Bazan, Silmeia Garcia [UNESP]; Barretti, Pasqual [UNESP]; Martin, Luis Cuadrado [UNESP]; Queluz, Thais Thomaz [UNESP] (Iranian Soc Nephrolgy, 2017)
Introduction. Pulmonary hypertension (PH) has been reported in hemodialysis patients, but data regarding its pathogenesis are scarce. This study aimed to evaluate the role of fluid overload in PH and its interrelationships with the usual biomarkers of micro-inflammatory state in hemodialysis patients. Materials and Methods. In is a cross-sectional and prospective study, 119 consecutive hemodialysis patients at a Brazilian referral university hospital were evaluated between March 2007 and February 2013. Based on the presence of echocardiographic parameters of PH, patients were allocated to two groups of the PH group and the non-PH group. Clinical parameters, site and type of vascular access, bio-impedance, and laboratory findings were compared between the two groups and a logistic regression model was elaborated. Results. Pulmonary hypertension was found in 23 (19.0%) of 119 patients. The groups significantly differed in extracellular water, ventricular thickness, left atrium diameter, and ventricular filling. Additionally, laboratory data associated with PH were alpha-1-acid glycoprotein (140.0 +/- 32.9 versus 116.0 +/- 35.5; P < .001); C-reactive protein (median, 1.1 versus 1.6; P = .01) and B-type natriuretic peptide (median, 328 versus 77; P = .03). The adjusted logistic regression model, including alpha-1-acid glycoprotein and B-type natriuretic peptide, showed significant associations for both (odds ratio, 1.023; 95% confidence interval, 1.008 to 1.043; P = .004 and odds ratio, 3.074; 95% confidence interval, 1.49-6.35; P = .002, respectively). Conclusions. Pulmonary hypertension, cardiac hypertrophy, fluid overload, and inflammation were associated to each other in hemodialysis patients, providing insight into its pathogenesis. Longitudinal studies are warranted.
Keywords: alpha-1-acid glycoprotein; B-type natriuretic peptide; end-stage renal disease; fluid overload; hemodialysis; inflammation; pulmonary hypertension